High-resolution nuclear magnetic resonance spectroscopic study of metabolites in the cerebrospinal fluid of patients with cervical myelopathy and lumbar radiculopathy - Nagashima, Hideki (Springer-Verlag, 2010)
There have been few reports describing substances related to oxidative and intermediary metabolism in the cerebrospinal fluid (CSF) in patients with spinal degenerative disorders. This study investigated whether the concentrations of metabolites in the CSF differed between patients with spinal degenerative disorders and controls, and whether the concentrations of these metabolites correlated with the severity of symptoms. CSF samples were obtained from 30 patients with cervical myelopathy (Group M), 30 patients with lumbar radiculopathy (Group R), and 10 volunteers (control). Metabolites in these CSF samples were measured by nuclear magnetic resonance spectroscopy. There were no differences in the concentrations of lactate, alanine, acetate, glutamate, pyruvate, or citrate between Groups M and R, between Group M and the control, or between Group R and the control. In Group M, neither symptom duration nor the Japanese Orthopaedic Association score correlated with the concentration of any metabolite. In Group R, the symptom duration positively correlated with the concentration of lactate, glutamate, and citrate in CSF. The duration of nerve root block showed a negative correlation with the concentrations of acetate in CSF of the patients in Group R. In patients with lumbar radiculopathy, there is a possibility of increased aerobic metabolic activity or decreased gluconeogenic activity in patients with shorter symptom duration, and increased aerobic metabolic activity in patients with severe inflammation around a nerve root.